STUDI KUANTITATIF ASPEK DEMOGRAFI TERHADAP JENIS STROKE - Wakano, Abuzar; Sulistiyani, Sulistiyani; Hardianti, Andi; Sendra, Eny (Ensiklopedia of Journal, 2025)
Abstract: Stroke is one of the non-communicable diseases that ranks second as the leading cause of death worldwide, after heart disease. Based on document reviews, the data on stroke cases at PON Hospital categorized by age and gender in 2023 shows 3,625 cases of ischemic stroke and 803 cases of hemorrhagic stroke. The purpose of this study was to determine the relationship between demographic aspects and stroke type. The study design used in this research was cross-sectional. The study was conducted at PON Hospital in September 2024. The population consisted of all stroke patients who visited the emergency department of the National Brain Center Hospital Prof. Dr. dr. Mahar Mardjono Jakarta. The sample consisted of 96 respondents. The sampling technique used was Simple Random Sampling. The research instrument used was a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results of the study showed a relationship between gender (p-value: 0.044) and age (p-value: 0.032) and stroke type. It is recommended that stroke patients undergo regular health check-ups to control existing risk factors and prevent the emergence of other stroke risk factors that could worsen the patient's condition and further increase the risk of recurrent stroke. Keywords: Gender, Stroke, Age.